Gladys Black letter to Nicholas S. Halmi regarding bird counts, February 23, 1977 - Black, Gladyset al (1977)
Bird counts of Snowy Owls and counts of Northern Shrike, Red-tailed Hawks and Kestrels in Lucas County contributed by Gladys Black in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologiests' Union Quarterly field report of winter 1976-1977. Epson - sheet feed/flatbed